Penerapan Data Mining Untuk Klasifikasi Kepuasan Pelanggan Transportasi Online (Ojek Online) Menggunakan Algoritma C.4.5 - Suherman Suherman; Donny Maulana; Vivi Mustikaningtyas (Prosiding Sains dan Teknologi, 2022)
Human activities to meet their daily needs and needs, both at work, or just for a walk. So, this needs to be supported by adequate transportation. With the development of technology today there are applications that introduce motorcycle taxi booking services using technology and use service standards. In Indonesia there are many motorbikes, which also function as general vehicles, namely transporting people / goods. Currently there are many online transportation service providers (online motorcycle taxi) known as Go-Jek, Grab, and Uber. Customer satisfaction input attributes in this study include price, facilities, service and loyalty. Data mining is a series of processes to explore added value in the form of information that has not been known manually from a database. In this study it is expected to help the online transportation services in increasing customer satisfaction. Based on the results of the classification using C4.5 algorithm shows that the accuracy reached 75.33%, which shows that the C4.5 algorithm is suitable for measuring the level of satisfaction of online transportation. Keywords: Satisfaction of online transportation, Data Mining, Algoritma C.4.5